Women's health: a study with lesbian college students (Research, Society and Development, 2022)
Objective: to identify health-related issues of college lesbians. Method: quantitative, cross-sectional and descriptive study, conducted online for a university student who declares herself a lesbian. With questions about social life, academic and women's health in the period from October 2021 to February 2022. Results: 35 college women between 19 and 34 years old participated, 29 of them were from the health area. Most of the women interviewed reported not being asked about sexual orientation by a health professional during gynecological consultations. However, they find some difficulties in performing the oncotic colpocytology exam, such as discomfort and pain. More than half of the sample reported that they are not afraid to expose their sexual orientation in the academic environment. In this way, eight participants reported having already suffered some prejudice at the university. Conclusion: The study identified that lesbian women take care of themselves, try to look for special care, but, in most cases, they still have doubts. It was found that health professionals do not know how to introduce the subject and even pass on information. In the academic environment, the subject is involved by myths and taboos. Everyone believes that it is a recurrent and normal theme; however, prejudice is still observed inside the classrooms. It is believed that health professionals and academics in training are not fully prepared for a specific care for lesbian women.